Betlehem in a Prophecy: Theological Analysis of Bethlehem in Micah 5:1-6 - Dwiraharjo, Susanto (Scriptura Indonesia, 2025)
Bethlehem is currently the subject of significant discussion and has frequently sparked debate. As a result, tensions have arisen among Christians, which often affects social relationships within the community of believers. This article aims to provide a biblical overview of the truth about Bethlehem to help reduce these tensions. To uncover this truth, we will employ exegesis, which involves thoroughly analysing the biblical text to reconcile differing interpretations and uncover the intended meaning. Through this analysis, we can deduce the significance of Bethlehem for us today and help the church to understand its importance in the context of Christ's redemptive work.